Pemanfaatkan Incenerator Limbah Infeksius: Upaya Menekan Penyebaran Covid-19 Kluster Sekolah - Eko Suhartono; Iwan Aflanie; Noor Muthmainah; Sumi Kartika (Universitas Lambung Mangkurat, 2022)
AbstractThe Covid-19 death rate in Banjarbaru Utara District ranks first, followed by Liang Anggang District. This requires an integrated effort from all elements of society to help suppress the spread of COVID-19 cases through community empowerment, including students in the school environment. SMK Telkom Banjarbaru is one of the schools located in the North Banjarbaru sub-district, which has the potential as a cluster for the spread of covid 19. In this regard, it is necessary to provide counseling about the spread of Covid-19 and incinerators as infectious waste processors. The method used is lecture, discussion, and question and answer. The activity was attended by 90 students and teachers, consisting of 81 students and 9 teachers. The training went smoothly. The participants were enthusiastic in listening to the presentation of the material, and were active in asking questions about the spread of Covid-19 and the processing of infectious waste. The conclusion of this activity was that the participants were motivated in the treatment of infectious waste. Keywords: incinerators, Covid-19, infectious waste, AbstrakTingkat kematian Covid-19 di Kecamatan Banjarbaru Utara menempati urutan pertama diikuti oleh Kecamatan Liang Anggang. Hal ini diperlukan upaya terpadu dari semua elemen masyarakat untuk membantu menekan penyebaran kasus covid-19 melalui pemberdayaan masyarakat, termasuk siswa di lingkungan sekolah. SMK Telkom Banjarbaru merupakan salah satu sekolah yang terletak di wilayah kecamatan Banjarbaru Utara, yang berpotensi sebagai kluster penyebaran covid 19. Berkaitan dengan hal itu perlu diberikan penyuluhan tentang penyebaran Covid-19 dan incinerator sebagai pengolah limbah infeksius. Metode yang digunakan adalah ceramah, diskusi, dan tanya jawab. Kegiatan diikuti oleh siswa dan guru sebanyak 90 peserta, yang terdiri atas 81siswa dan 9 guru. Penyuluhan berjalan dengan lancar. Para peserta antusias dalam mendengarkan pemaparan materi, dan aktif dalam tanya jawab seputar penyebaran Covid-19 dan pemgolahan limbah infeksius. Kesimpulan kegiatan ini para peserta penyuluhan termotivasi dalam pengolahan limbah infeksius. Kata kunci: incinerator, Covid-19, limbah infeksius,